Endometrial autotransplantation in rabbits: Potential for fertility restoration in severe Asherman's syndrome. (May 2020) - Jones, Benjamin P.; Vali, Saaliha; Saso, Srdjan; Garcia-Dominguez, Ximo; Chan, Maxine; Thum, Meen-Yau; Ghaem-Maghami, Sadaf; Kaur, Baljeet; García-Valero, Luís; Petrucci, Linda; Yazbek, Joseph; Vicente, Jose S.; et al.
Abstract: Objective: Uterine transplantation is now considered a feasible treatment for women with absolute uterine factor infertility and has been successfully performed for a woman with Asherman's syndrome (AS). The endometrium is a clinically and histologically distinct entity from the surrounding myometrium. Endometrial transplantation (ETx) may offer a less invasive option, with less immunogenic impact, to restore fertility in women with severe AS. The objective of this study was to assess the feasibility of ETx by evaluating surgical and reproductive outcomes following endometrial autotransplantation in a rabbit model. Study design: A longitudinal study assessing surgical, biochemical, radiological, reproductive and histological outcomes following endometrial autotransplantation in ten New Zealand white rabbits. Results: Ten procedures were performed, including 8 endometrial auto-transplants (ETx) and 2 endometrial resections (ER), to control against endometrial regeneration. Eight procedures were successful, whereas two rabbits from the ETx group died intra-operatively. Three rabbits were euthanised at 48, 72 and 96 h post-operatively to assess gross and histological appearances. Two rabbits, one from the ETx group and one from the ER group, died four weeks and eight weeks post-operatively. Three rabbits subsequently underwent two cycles of in-vitro fertilization. The first cycle resulted in an implantation rate of 57% in the un-operated uteri. In two rabbits who underwent ETx, an implantation rate of 28.6% was seen. In the second cycle, an implantation rate of 61.9 % (13 implantations) was observed in the control uteri. In the two ETx females, an implantation rate of 14.3 % was seen. No pregnancies were seen in either cycle in the animals who underwent ER. Despite successful implantations in both cycles in the ETx rabbits, no livebirths were achieved. Following death or euthanasia there was gross and microscopic evidence of viable endometrium following ETx, but not following ER. Conclusion: This study has revealed, for the first time, the feasibility of ETx with gross and microscopic evidence of viable endometrium, and the demonstration of clinical pregnancies. Whilst further studies are essential, and the achievement of successful livebirths fundamental, ETx may offer a potential fertility restoring opportunity for women with severe, treatment refractory cases of AS.